1982
DOI: 10.1203/00006450-198202000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Function in the Reserpinized Rabbit—a Model for Cystic Fibrosis. I. Effect of Secretin

Abstract: Summaryby CF, ~ancreatic secretions have not been as extensively studiedPancreatic juice was collected from rabbits treated with reserpine and from untreated controls. The volume of pancreatic juice secreted, flow rate and the bicarbonate output were all significantly reduced in the treated animals during both spontaneous flow and during secretin-stimulated flow. On the other hand, the total protein concentration, the amylase activity and the calcium concentration of the pancreatic juice were all significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…It is important to note, however, that despite the presence of the factor, the total bicarbonate output in the juice of reserpinized rabbits was significantly less than that observed for controls (Table 2). This observation confirms previous studies made in reserpinized rabbits (17) and rats (14). By contrast, the bicarbonate ouput after retroperfusion with substances containing known transport inhibitory properties was elevated over that of controls (Table 2); thus, the reduced bicarbonate output must have been secondary to the reduced volume of pancreatic juice secreted by the reserpinized animals (Table 1) (14,16,17).…”
Section: Relationship Of Bicarbonate Concentration To Pancreaticflow supporting
confidence: 72%
See 3 more Smart Citations
“…It is important to note, however, that despite the presence of the factor, the total bicarbonate output in the juice of reserpinized rabbits was significantly less than that observed for controls (Table 2). This observation confirms previous studies made in reserpinized rabbits (17) and rats (14). By contrast, the bicarbonate ouput after retroperfusion with substances containing known transport inhibitory properties was elevated over that of controls (Table 2); thus, the reduced bicarbonate output must have been secondary to the reduced volume of pancreatic juice secreted by the reserpinized animals (Table 1) (14,16,17).…”
Section: Relationship Of Bicarbonate Concentration To Pancreaticflow supporting
confidence: 72%
“…This is due to a positively charged transport inhibitory factor (13). The pancreas of reserpine-treated rats and rabbits secrete reduced amounts of juice which contains elevated amounts of protein but a decreased bicarbonate output (14,17). In this study, the pancreatic juice secreted by treated rabbits was also shown to contain a decreased bicarbonate output (Table 1) but an elevated bicarbonate concentration (Fig.…”
Section: Relationship Of Bicarbonate Concentration To Pancreaticflow mentioning
confidence: 59%
See 2 more Smart Citations
“…Early studies in anaesthetized animals showed it to possess a true spontaneous secretion (5), which could be augmented by vagal stimulation or intravenous acetylcholine (6). Between 1965 and the present, a number of studies have been published on anaesthetized rabbit, in which some aspects of pancreatic electrolyte secretion have been measured (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In these studies, very considerable variations in the volume and composition of spontaneous and secretin-stimulated pancreatic juice are recorded, while in only four has the effect of CCK on fluid secretion been briefly mentioned (9,13, 16,18).…”
mentioning
confidence: 99%